Analysis Ability Literacy Mathematics Reviewed from Self Efficacy Junior High School Students - Nada, Yusrina Qotrun; Yulianto, Alfany Rahman; Iffah, Rona Dhiya Layli (International Journal of Research in Mathematics Education, 2024)
study in study This to explain about ability literacy mathematics participant reviewed education from self efficacy. Research This aiming for analyze and describe ability literacy mathematics based on self efficacy participant educate with category high, medium, and low. Research This conducted at PKBM Homeschooling HSPG Purwokerto . Subject study this is participant educate 9th grade of junior high school. Taking sample use propositional sampling with take subject in accordance with topics developed. Data collection techniques with use questionnaire, test written, and interviews. While data analysis using analysis qualitative descriptive for describe in detail related ability analysis mathematics reviewed from self efficacy. Research results mention that participant educate with self efficacy tall own ability literacy good mathematics, thing that proven with results workmanship systematic questions. While the participantsstudents who have ability self efficacy currently own ability enough math well, some indicator literacy mathematics can done with good although Still there are some who haven't maximum. Then the participants educate with self efficacy low own ability literacy very poor mathematics, thing that proven with less results in every indicator evaluation literacy mathematics. Based on results study that self efficacy influence ability literacy mathematics participant educate, because self efficacy play a role important in build belief participant educate in to his ability in finish question mathematics .